(untitled) (Asian Journal of Medical and Biological Research, 2022)
The agriculture industry is widely believed to be essential to the nation’s long-term growth and prosperity. In many ways, including via enhanced food security, employment, and economic growth, the agricultural sector as a whole and fisheries in particular have made significant contributions to enhancing people’s health and well-being. A variety of measures may be used to determine the financial health of the fish farms. The purpose of this study was to estimate the financial viability of fish pond farming and to ascertain its advantages and disadvantages. From the Taltoli upazila in the Barguna area, sixty pond fish breeders were randomly selected. These figures allow us to calculate the gross cost of producing pond fish per hectare to be 1378806 BDT, the gross return to be 2125023 BDT, and the net return to be 746217 BDT. The findings of this study proved that pond fish farming was a profitable endeavor in the region that was being studied. The Cobb-Douglas production function was further employed in order to better comprehend the part that each variable in the production of pond fish plays. The majority of the taken into account factors were demonstrated to have a considerable impact on fish productivity. The returns on pond fish production were positively and statistically significantly impacted by four of the six parameters studied. To improve the management and cultivation of pond fish farming, certain recommendations were made. Asian J. Med. Biol. Res. 2022, 8 (4), 240-250